Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1111/j.1439-0434.2006.01189.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seed Treatment with Rhizobium leguminosarum on Pythium Damping‐off, Seedling Height, Root Nodulation, Root Biomass, Shoot Biomass, and Seed Yield of Pea and Lentil

Abstract: Field experiments were conducted in 2004 and 2005 to determine the effects of seed treatment with Rhizobium leguminosarum bv. viceae on damping-off, seedling height, root nodule mass, root biomass, shoot biomass and seed yield of pea and lentil in a field naturally infested with Pythium spp. Compared with the untreated controls, treatment of pea seeds with R. leguminosarum bv. viceae strains R12, R20 or R21 significantly (P < 0.05) reduced incidence of dampingoff, promoted seedling growth and increased root no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 16 publications
(24 reference statements)
2
42
0
Order By: Relevance
“…Other reports from Italy also indicated that two isolates of rhizobia induced a significant improvement of grain yield of lentil from 37% to 40% with respect to non-inoculated plants [28]. Moreover, several reports demonstrated that significantly higher yield in lentil was due to N 2 fixation [13,29,30]. Note: plt-per plant, PlH-plant height, NB-number of branch, NP-number of pod, GY-grain yield, GW-grain weight.…”
Section: Grain Yield and Yield Componentsmentioning
confidence: 95%
“…Other reports from Italy also indicated that two isolates of rhizobia induced a significant improvement of grain yield of lentil from 37% to 40% with respect to non-inoculated plants [28]. Moreover, several reports demonstrated that significantly higher yield in lentil was due to N 2 fixation [13,29,30]. Note: plt-per plant, PlH-plant height, NB-number of branch, NP-number of pod, GY-grain yield, GW-grain weight.…”
Section: Grain Yield and Yield Componentsmentioning
confidence: 95%
“…in both leguminous and nonleguminous plants under field conditions (Haque and Ghaffar, 1993). Huang and Erickson (2007) observed significantly reduced incidence of damping-off, promoted seedling growth and increased root nodule mass, plant biomass and seed yield of pea and lentil due to Elkoca et al (2008) observed that seed inoculation of chickpea with Rhizobium significantly increased the seed yield under different inoculation treatments which ranged between by 18.0% to 30.5 % over the control.…”
Section: Resultsmentioning
confidence: 98%
“…They observed that fungal inhibition was more pronounced in dual culture conditions in comparison to that of cell free culture filtrate. Huang and Erickson (2007) proved that seed treatment with R. leguminosarum b.v. viceae was effective in controlling damping off in pea under naturally infested field condition. Mazen et al (2008) evaluated the antagonistic activities of the cultural filtrates of R. leguminosarum and arbuscular mycorrhiza (AM) fungi in the management of damping off and root rot diseases of faba bean.…”
Section: Resultsmentioning
confidence: 99%
“…Amongst the environmental factors modifying seed mass, weather and soil conditions are very important. Huang and Erickson (2007) showed that inoculation of pea seeds triggers several changes in morphological features and improves seed yield, whereas Zając et al (2013) did not observe any significant reaction of the plant to inoculation. Zając et al (2013) proved that the single seed mass significantly depends on the seed position in a pod with the seeds located in the central part of the pod having a larger mass and that the number of seeds in the pod is influenced by the node position on the stem.…”
Section: Introductionmentioning
confidence: 98%